2022
DOI: 10.3390/buildings12122100
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Sentiment and Office Markets: Evidence from China

Abstract: This study examines the impact of COVID-19 sentiment on office building rents and vacancy rates in China with a COVID-19 sentiment index constructed based on Baidu search queries on COVID-19-related keywords. We analyzed the data of office buildings and economic data from 2013 Q3 to 2022 Q2 in seven major Chinese cities with a two-stage Error Correction Model framework. We found that a heightened level of COVID-19 sentiment significantly and adversely affects the Chinese office buildings market. Specifically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 65 publications
0
0
0
Order By: Relevance
“…Finally, considering that the face-to-face interviews were conducted prior to the COVID-19 pandemic, the impacts of the COVID-19 pandemic on senior housing development have not been fully considered in the present study. In addition to the penetration of new technologies, empirical studies have also found that the COVID-19 pandemic had a significant influence on housing markets in terms of vacancy rate [142], housing price [143], housing affordability [144], and housing demand [145]. Therefore, a future study in the post-COVID environment is needed to explore how political, economic, social, and technological factors could influence senior housing development in the post-pandemic era.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, considering that the face-to-face interviews were conducted prior to the COVID-19 pandemic, the impacts of the COVID-19 pandemic on senior housing development have not been fully considered in the present study. In addition to the penetration of new technologies, empirical studies have also found that the COVID-19 pandemic had a significant influence on housing markets in terms of vacancy rate [142], housing price [143], housing affordability [144], and housing demand [145]. Therefore, a future study in the post-COVID environment is needed to explore how political, economic, social, and technological factors could influence senior housing development in the post-pandemic era.…”
Section: Discussionmentioning
confidence: 99%
“…Third, there were limits to the frequency of observations recorded in the field for this study. More recent public health and real estate research papers are beginning to fill this gap by examining impacts over longer periods of time (Lee et al, 2021;Carozzi et al, 2022;Guo et al, 2023;Kiaghadi et al, 2022;Motoyama, 2022;Wang et al, 2022a;Wu et al, 2022;Tsou et al, 2023). Fourth, as a study of urban neighborhoods, zoned for growth, in a US city, at the center of a metropolitan area, there are limits to the generalizability of this work and its findings.…”
Section: Discussionmentioning
confidence: 99%
“…The onset of the COVID-19 pandemic has had a significant impact on the broader economy and property markets [49,50]. As the COVID-19 pandemic began to affect global economies, governments across advanced economies developed substantial economic stimulus programs.…”
Section: The Covid-19 Economic Crisismentioning
confidence: 99%